The future treatment for type 1 diabetes: Pig islet- or stem cell-derived β cells? - Naqvi, Raza Ali; Naqvi, Afsar Raza; Singh, Amar; Priyadarshini, Medha; Balamurugan, Appakalai N.; Layden, Brian T. (Frontiers in Endocrinology, 2023)
Replacement of β cells is only a curative approach for type 1 diabetes (T1D) patients to avoid the threat of iatrogenic hypoglycemia. In this pursuit, islet allotransplantation under Edmonton’s protocol emerged as a medical miracle to attain hypoglycemia-free insulin independence in T1D. Shortage of allo-islet donors and post-transplantation (post-tx) islet loss are still unmet hurdles for the widespread application of this therapeutic regimen. The long-term survival and effective insulin independence in preclinical studies have strongly suggested pig islets to cure overt hyperglycemia. Importantly, CRISPR-Cas9 technology is pursuing to develop “humanized” pig islets that could overcome the lifelong immunosuppression drug regimen. Lately, induced pluripotent stem cell (iPSC)-derived β cell approaches are also gaining momentum and may hold promise to yield a significant supply of insulin-producing cells. Theoretically, personalized β cells derived from a patient’s iPSCs is one exciting approach, but β cell-specific immunity in T1D recipients would still be a challenge. In this context, encapsulation studies on both pig islet as well as iPSC–β cells were found promising and rendered long-term survival in mice. Oxygen tension and blood vessel growth within the capsules are a few of the hurdles that need to be addressed. In conclusion, challenges associated with both procedures, xenotransplantation (of pig-derived islets) and stem cell transplantation, are required to be cautiously resolved before their clinical application.